A comparative evaluation of DIAGNOdent with visual and radiography for detection of occlusal caries: An in vitro study - Sridhar N; Tandon S; Rao Nirmala (Wolters Kluwer Medknow Publications, 2009)
Background: The diagnosis of dental caries is fundamental to the practice of dentistry. Despite the fact that dental caries has declined considerably, it is still a problem of great importance. The reduction in caries prevalence has not occurred uniformly for all the surfaces. The greatest reduction was observed at lesions located on smooth surfaces, so that occlusal caries are most common in children. Aim: The purpose of this study is to determine the clinical efficacy of DIAGNOdent in detecting occlusal caries. Materials and Methods: A total number of 50 teeth were subjected for visual, radiographic, and DIAGNOdent examinations. All the three methods were compared to histology which is a gold standard. Results: The result obtained showed that DIAGNOdent is superior to visual and radiographic methods in diagnosing occlusal caries.